(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
Unfortunately, a baby’s cold is not a rare condition. Babies are almost immune to any virus. It should be noted that breastfed babies are less susceptible to ARVI than babies who use special formulas.